Morphological Characterization of Goat Populations in Central Zone of Tigray, Ethiopia - Birhanie, M.; Alemayehu, K.; Mekuriaw, G. (Tropical Animal Science Journal, 2019)
Ethiopia has huge livestock resource, but poor in their productivity. It stated national small ruminant breeding policy and strategy focused on genetic improvement. This is intended to design appropriate breeding programs based on the indigenous breeds status. Study of phenotypic variation is among the prerequisite activities of genetic improvement that is limited in this study area. The objective of this study was to describe morphological characteristics and variations of goat populations in the Central zone of Tigray. Qualitative and quantitative data of 403 young to matured goats (326 lactating does and 77 bucks) were used to analyze by frequency procedure, GLM procedure, Pearson correlation, and multivariate analysis of SAS version 9.4. The study revealed that goats in Adwa district were distinct in coat colors and pattern, horn shape, ear orientation, head profile and ruff, significantly heavier (p